The Role of Job Stress in the Effect of Workplace Incivility on Organizational Commitment; İşyeri nezaketsizliğinin örgütsel bağlılığa etkisinde İş stresinin rolü - İlkay Güleryüz; Lütfi Sürücü; İbrahim Yikilmaz (Erciyes İletişim Dergisi, 2023)
Organizations must prioritize issues related to organizational behavior to achieve important gains, such as fulfilling organizational objectives and providing sustainable competitive advantages. This study's focus point is to analyze the impact of workplace incivility on organizational commitment and job stress. A unique model has been proposed that deals with workplace incivility, organizational commitment and job stress. To test this model, a survey method was utilized to collect data from individuals working in the furniture sector in the province of Kayseri (N=384). The collected data were analyzed using AMOS-22 and SPSS-27 package programs. The hypothesis tests performed with the regression-based Process Macro analysis showed workplace incivility had statistically significant positive impact on job stress, while it had a statistically significant negative impact on organizational commitment. We conducted a study on the relationship between workplace incivility and organizational commitment and analyzed the mediating role of job stress in this connection. This constitutes the original aspect of the present study. The results suggest relationship between of these two variables is mediates by job stress, revealing the originality of the proposed research model. This empirical study's findings make a significant contribution to literature by illustrating the issues that workplace incivility affects, particularly organizational behavior and work stress. Additionally, examining workplace incivility together with different organizational behavior issues is considered to make important contributions to both business management and academic literature. – – Örgütler, örgütsel amaçları gerçekleştirmek ve sürdürülebilir rekabet avantajı sağlamak gibi önemli kazanımlar elde etmek için örgütsel davranışla ilgili konulara öncelik vermelidir. Bu çalışma, işyeri nezaketsizliğinin iş stresi ve örgütsel bağlılık üzerindeki etkilerine odaklanmaktadır. İşyeri nezaketsizliği, iş stresi ve örgütsel bağlılık ile ilgilenen özgün bir model önerilmiştir. Bu modeli test etmek için Kayseri ilinde mobilya sektöründe çalışanlardan anket yöntemi (N=384) kullanılarak veriler toplanmıştır. Toplanan veriler AMOS-22 ve SPSS-27 paket programları kullanılarak analiz edilmiştir. Regresyon tabanlı Process Makro analizi ile yapılan hipotez testleri, işyeri nezaketsizliğinin iş stresi üzerinde istatistiksel olarak anlamlı pozitif bir etkiye sahip olduğunu, örgütsel bağlılık üzerinde ise negatif ve anlamlı bir etkiye sahip olduğunu göstermiştir. Bu araştırmanın özgün yanını oluşturan işyeri nezaketsizliği ile örgütsel bağlılık arasındaki ilişkide iş stresinin aracı rolü incelenmiştir. Bu iki değişken arasındaki ilişkide iş stresinin aracılık rolüne sahip olması önerilen araştırma modelinin özgünlüğünü ortaya koymaktadır. Bu ampirik çalışmanın bulguları, işyeri nezaketsizliğinin etkilediği konuları, özellikle örgütsel davranış ve iş stresini vurgulayarak literatüre katkıda bulunmaktadır. Ayrıca işyeri nezaketsizliğinin farklı örgütsel davranış konuları ile birlikte incelenmesinin hem işletme yönetimine hem de akademik literatüre önemli katkılar sağlayacağı düşünülmektedir
Keywords: 330; Workplace Incivility; Job Stress; Organizational Commitment